Zinc Oxide Thin Film Transistors: Advances, Challenges and Future Trends - Kandpal, Kavindra; Gupta, Navneet (Bulletin of Electrical Engineering and Informatics, 2016)
This paper presents a review on recent developments and future trends in zinc oxide thin film transistors (ZnO TFTs) together with challenges involved in this technology. It highlights ZnO TFT as next generation choice over other available thin film transistor technology namely a â Si: H (amorphous hydrogenated silicon), poly-Si (polycrystalline silicon) and OTFT (organic thin film transistor). This paper also provides a comparative analysis of various TFTs on the basis of performance parameters.Â  Effect of high âk dielectrics, grain boundaries, trap densities, and threshold voltage shift on the performance of ZnO TFT is also explained.